2008
DOI: 10.1007/s11243-008-9163-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and spectroscopic characterization of iron(II) and copper(II) complexes of a functionalized crown ether

Abstract: Condensation between 4 0 -aminobenzo-15-crown-5-and 4-antipyrinecarboxaldehyde yielded the functionalized crown ether (L = 1,5-dimethyl-4- [(2,3,5,6,8,9,11,12-octahydro-1,4,7,10,13-benzopentaoxacyclopentadecin-A 1:1 (Na ? :L) complex has been prepared. The reaction of Fe(II) and Cu(II) salts with L gave complexes of composition [Fe(L)Cl 2 ] and [Cu(L) 2 Cl 2 ]. Heteronuclear complexes [Fe(L)Cl 2 Na]ClO 4 and [Cu(L) 2 Cl 2 Na]ClO 4 have also been synthesized from the reactions of [Fe(L)Cl 2 ] and [Cu(L) 2 Cl 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…10 H] groups, respectively. All of the mass spectra show that this fragmentation pattern proceeding by the loss of etheric chains is in accordance with the literature [26][27][28]. The molecular ion peaks and fragments of the ligands and complexes support the proposed structures.…”
Section: Mass Spectrasupporting
confidence: 88%
“…10 H] groups, respectively. All of the mass spectra show that this fragmentation pattern proceeding by the loss of etheric chains is in accordance with the literature [26][27][28]. The molecular ion peaks and fragments of the ligands and complexes support the proposed structures.…”
Section: Mass Spectrasupporting
confidence: 88%
“…Although bi-dentate chelating compounds were investigated in plentiful studies, only one of them has been reported on benzo crown ether-4-antipyrine containing Schiff base group. Regarding this property, Hayvali 80 , 2009, reported the preparation of a novel crown antipyrine azomethine (Figure 20).…”
Section: Scheme 16 Synthesis Route Of Ligands and Their Complexes Mncilmentioning
confidence: 99%
“…6,[13][14][15] The crown ether center can generate stable complexes with alkali metal and alkaline earth metal cations, while the substituted side center can form transition metal complexes. 12,[16][17][18][19][20][21][22][23] Their complexing properties make crown ethers especially interesting and useful compounds in biological research and in chemistry. [24][25][26][27][28][29][30][31] The ion complex-carrying ability of crown ethers results in them resembling natural ionophores (such as gramicidin).…”
Section: Introductionmentioning
confidence: 99%